2019
DOI: 10.5539/jas.v11n14p254
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic Acid and K-Phosphite Enhance Productivity and Technological Quality of Sugarcane Crop

Abstract: Plant resistance inducers are cost-effective and environmentally pleasing strategies of plant protection to mitigate biotic and abiotic agents threatening food safety and energy security. We, accordingly, present jasmonic acid and k-phosphite as low-cost strategies to enhance productive yield and technological quality of sugarcane crop. Exogenously treatment of the sugarcane variety ‘SP81-3250’ consisted of carrying out foliar application of jasmonic acid at 1, 1.5 and 2 ml L-1 and K-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Additionally, potassium phosphite produced potato tubers with higher values of N, P, K, starch and carbohydrtaes and that might be due to the role of phosphite in improving N mobilization resulting in a higher nutrient efficiency (Swarup et al, 2020). Furthermore, in sugarcane, K-phosphite probably improves soluble solids availability by releasing water-soluble inorganic ions like P and K, and signaling of phytoalexins synthesis and antimicrobial secondary metabolites which protect plants from pathogens (Moreira et al, 2019). In potato, Achary et al (2017) found that phosphite foliar treatment increased pectin content and polygalacturonase activity and induced the formation of a new chitinase isoform in tubers.…”
Section: Tuber Qualitymentioning
confidence: 99%
“…Additionally, potassium phosphite produced potato tubers with higher values of N, P, K, starch and carbohydrtaes and that might be due to the role of phosphite in improving N mobilization resulting in a higher nutrient efficiency (Swarup et al, 2020). Furthermore, in sugarcane, K-phosphite probably improves soluble solids availability by releasing water-soluble inorganic ions like P and K, and signaling of phytoalexins synthesis and antimicrobial secondary metabolites which protect plants from pathogens (Moreira et al, 2019). In potato, Achary et al (2017) found that phosphite foliar treatment increased pectin content and polygalacturonase activity and induced the formation of a new chitinase isoform in tubers.…”
Section: Tuber Qualitymentioning
confidence: 99%
“…As environmentally friendly compounds, JA is expected to replace pesticides used in agriculture by helping plants to defend against the invasions of pathogens and pests [ 1,2 ] and can be used to improve plant stress resistance and fruit storage after ripening. [ 3–5 ] In addition, these compounds are highly important in the perfume industry owing to their jasmine fragrance and are typically used in high‐end perfumes, shampoos, and detergents [ 6 ] as well as in cigarettes and chewing gum. Moreover, JAs have shown anticancer activity against various types of tumors and thus have potential in the treatment of cancer‐related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, JAs play an important role in agriculture nowadays by regulating the defence of plants against pests and pathogens ( Gális et al, 2009 ; Gavin et al, 2012 ; Hawkins et al, 2007 ; Heil et al, 2001 ; Moreira et al, 2019 ; Rohwer & Erwin, 2008 ; Sanches et al, 2017 ; Stout, Zehnder & Baur, 2002 ; Wasternack, 2014 ). Their application seems to be in line with the principles of sustainable agriculture since they may be less aggressive to the environment than pesticides and mineral fertilizers ( Secatto, 2013 ).…”
Section: Introductionmentioning
confidence: 99%